Impact of institutional organization on research productivity and multidisciplinarity - García-Rodríguez, Alberto; Barrio, R. A.; Govezensky, Tzipe; Tagüeña, Julia; Pérez, Miguel Robles; Calvet, Humberto Carrillo; Jiménez Andrade, José Luis; Arencibia-Jorge, Ricardo; Kaski, Kimmo (Frontiers in Physics, 2023)
In this article, we will describe a model to examine the influence of differently organized institutions on their scientific productivity. We take two extreme cases, on one hand, an institution divided in departments with no collaboration between people in different departments. These could be disciplines or merely projects. On the other hand, we consider an institution that allows interactions between all individuals, without a departmental structure to a department. We compare the results with data from the Institute of Renewable Energy (IER) at UNAM, which has changed its organization and policies during the last 30 years, and we could quantitatively predict the changes observed in productivity and multidisciplinarity. This model can be applied to a broader set of institutions and processes.